Controlled Release: A Chemical Display: Generating Animations by Controlled Diffusion from Porous Voxels (Adv. Funct. Mater. 26/2015). (July 2015) - Kalinin, Yevgeniy V.; Pandey, Shivendra; Hong, Jinpyo; Gracias, David H.
<x xml:space="preserve">Abstract</x> Porous chemically loaded voxels can be dispensed in arrays on both rigid and flexible substrates to enable dynamic patterns and provide proof‐of‐concept for a chemical display. Simulations and experiments which are used to design the animation of a running man are described by D. H. Gracias and team on page 3998. Graphics: Jinpyo Hong and Martin Rietveld.